Program Parenting Di TK Negeri Pembina Kota Tasikmalaya - Fadila Rahmah; Putri Chaerunnisa; Rahma Sukmara Putri; Purwati Purwati; Tasya Nur Ramdhani; Heri Yusuf Muslihin (UIN Sultan Maulana Hasanudin Banten, 2023)
Early age is a golden period where all activities that children carry out at that time can affect the future, one of which is the parenting style applied by parents and the environment which will affect children’s development. Therefore, parents must instill good parenting styles for their children. Not only parents, PAUD institutions also need to carry out learning and parenting programs for parents so that the parenting style applied by parents and teachers is the same so that children’s development will be more optimal. The purpose of this research is to find out how the parenting program is implemented at TKN Pembina Tasikmalaya. The method used is qualitative which is carried out with in-depth interviews, so that researchers obtain clearer data. From the results of the interviews, it can be concluded that the Tasikmalaya TKN Pembina can be said to be quite good at implementing parenting programs.